Promoting Wellbeing at Work – Case of Professional Kitchens (Reabilitacijos mokslai: slauga, kineziterapija, ergoterapija, 2026)
Professional kitchens are working environments characterised by a high workload, stemming from repetitive upper-limb movements, handling heavy and hot cauldrons, and spending long periods on one’s feet. In addition to the physical demands, kitchen work involves considerable cognitive load due to constant interruptions, multitasking, and the need for rapid decision-making. As the workforce ages, the demand for interventions that improve working conditions and support longer, healthier careers is growing. From a broader perspective, productivity has increased in many industrial sectors over the recent decades, yet this development has not extended to this service industry. The vast majority of food service SMEs are small enterprises with fewer than ten employees, and their profitability is currently under significant pressure due to economic uncertainty. In this context, improving work conditions to support both productivity and wellbeing at work requires comprehensive, integrated approaches.Our project, “Professional Kitchens and Catering – KetCat”, responds to these challenges by developing practical, evidence-based solutions that enhance workability and promote sustainable wellbeing in professional kitchens. Built on participatory development methods, the project recognises that kitchen staff have unique insights into workflow inefficiencies, sources of physical strain, and daily obstacles that affect their ability to work well. Through workshops, workplace assessments, and co-design sessions, the project supports employees and managers in jointly identifying critical pain points and generating feasible solutions within the realities of small enterprises.A central focus is reducing unnecessary physical load and streamlining work processes through ergonomic improvements, redesigned task flows, and clearer division of responsibilities. Equally important are psychosocial aspects of wellbeing: predictable work rhythms, transparent communication, and opportunities to influence one’s own work strengthen motivation and reduce cognitive overload. By integrating both physical and psychosocial dimensions, the project advances a comprehensive model of workability tailored to the kitchen sector. In conclusion, improving working conditions is not a cost but an investment: when staff experience less strain, smoother workflows, and greater control over their tasks, both productivity and job satisfaction increase – outcomes that are essential for the long-term resilience and sustainable performance of small enterprises.Keywords: Professional kitchens; intervention; ergonomics; workability; productivity